Culture in 10% O2 enhances the production of active hormones in neuro-endocrine cells by up-regulating the expression of processing enzymes. Issue 5 (12th March 2019) - Sato, Eri; Maeda, Yoshinori; Sato, Yui; Hinata, Airi; Gomi, Hiroshi; Koga, Daisuke; Torii, Seiji; Watanabe, Tsuyoshi; Hosaka, Masahiro
Abstract : To closely mimic physiological conditions, low oxygen cultures have been employed in stem cell and cancer research. Although in vivo oxygen concentrations in tissues are often much lower than ambient 21% O2 (ranging from 3.6 to 12.8% O2 ), most cell cultures are maintained at 21% O2 . To clarify the effects of the O2 culture concentration on the regulated secretion of peptide hormones in neuro-endocrine cells, we examined the changes in the storage and release of peptide hormones in neuro-endocrine cell lines and endocrine tissues cultured in a relatively lower O2 concentration. In both AtT-20 cells derived from the mouse anterior pituitary and freshly prepared mouse pituitaries cultured in 10% O2 for 24 h, the storage and regulated secretion of the mature peptide hormone adrenocorticotropic hormone were significantly increased compared with those in cells and pituitaries cultured in ambient 21% O2, whereas its precursor proopiomelanocortin was not increased in the cells and tissues after being cultured in 10% O2 . Simultaneously, the prohormone-processing enzymes PC1/3 and carboxypeptidase E were up-regulated in cells cultured in 10% O2, thus facilitating the conversion of prohormones to their active form. Similarly, culturing the mouse β-cell line MIN6 and islet tissue in 10% O2 also significantly increased the conversion of proinsulin into mature insulin, which was secreted in a regulated manner. These results suggest that culture under 10% O2 is more optimal for endocrine tissues/cells to efficiently generate and secrete active peptide hormones than ambient 21% O2 .